Donepezil protects glycerol-induced acute renal failure through the cholinergic anti-inflammatory and nitric oxide pathway in rats. (1st November 2020) - Sun, Guodong; Wang, Jialei; Wang, Pan; Ren, Huimin; Yue, Yuedong; Song, Zhengmin; Fu, Xiaobin
Abstract: Objectives: Inflammation as well as oxygen metabolite play important roles in renal injury during pathogenesis of rhabdomyolysis induced myoglobinuric acute renal failure (ARF). The aim of this study was to investigate the protective effects of donepezil on immune responses in rats with glycerol-induced ARF. Methods: Sixty male rats were randomly divided into six groups, the rats were given normal saline (10 ml/kg, i.m.), glycerol (50%, 10 ml/kg, i.m.), glycerol plus dexamethasone (0.1 mg/kg, i.g.), and glycerol plus donepezil (1, 5 and 10 mg/kg, i.g.) respectively. After two weeks of glycerol injections, the kidney tissues and blood samples were harvested for future biochemical and pathology analysis. The levels of creatinine (Cr) and urea nitrogen (BUN) in plasma, the content of malondialdehyde (MDA), glutathione (GSH), and superoxide dismutase (SOD) activity, total nitric oxide synthase (TNOS), inducible nitric oxide synthase (iNOS), endothelial NO synthase (eNOS) were evaluated in renal tissues. In addition, interleukin-6 (IL-6), tumor necrosis factors-α (TNF-α) in renal tissues were also determined. Results: Donepezil treatment protected rats from renal dysfunction in a dose-dependent manner and through the cholinergic anti-inflammatory pathway. Additionally, donepezil significantly reduced tubular damages, prevented neutrophil infiltration and decreased productions of the IL-6, TNF-α, nitric oxide content and oxidative damage. Conclusions: These data indicate that donepezil exerts a protective anti-inflammatory effect during ARF through the cholinergic pathway and Nitric oxide pathway. In addition, this study could provide an opportunity to overcome the effect of surgical cholinergic denervation during kidney transplantation and other injury.